Stella Batts : who's in charge? - Sheinmel, Courtney (Sheinmel, Courtney. Stella Batts, 2013)
"Stella volunteers to watch best friend Evie's dog, Bella, for a few days. Disaster strikes when Bella gets loose and runs away. Stella must find her before Evie returns"--